2004
DOI: 10.1038/ng1359
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and the Tel1 and Mec1 checkpoints differentially effect genome rearrangements driven by telomere dysfunction in yeast

Abstract: In telomerase-deficient Saccharomyces cerevisiae, telomeres are maintained by recombination. Here we used a S. cerevisiae assay for characterizing gross chromosomal rearrangements (GCRs) to analyze genome instability in post-senescent telomerase-deficient cells. Telomerase-deficient tlc1 and est2 mutants did not have increased GCR rates, but their telomeres could be joined to other DNAs resulting in chromosome fusions. Inactivation of Tel1 or either the Rad51 or Rad59 recombination pathways in telomerase-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
70
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 30 publications
7
70
0
Order By: Relevance
“…The PI3K-related protein kinases Tel1 and Mec1 control DNA damage checkpoints during cell cycle so that their deletion or inhibition elicits hypersensitivity to DNA-damaging agents (35)(36)(37). Earlier, we showed that inositol pyrophosphates are required for DNA hyper recombination in certain yeast (38).…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K-related protein kinases Tel1 and Mec1 control DNA damage checkpoints during cell cycle so that their deletion or inhibition elicits hypersensitivity to DNA-damaging agents (35)(36)(37). Earlier, we showed that inositol pyrophosphates are required for DNA hyper recombination in certain yeast (38).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies using this approach have demonstrated that there are eight pathways for suppressing these chromosomal aberrations, while six pathways promote GCR formation. The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of MEC1 and TEL1 are known to cause substantial increases in gross chromosomal rearrangements (GCRs) (10 -12). Although telomere fusion is thought to contribute to chromosomal rearrangements observed in the mec1⌬ tel1⌬ mutant, loss of telomerase alone does not cause similar chromosomal rearrangements (11,12), indicating that defective DNA repair might also be involved. Despite the fact that many substrates of Mec1 and Tel1 have been identified, a major challenge has been to identify and characterize those Mec1/ Tel1 substrates whose phosphorylation specifically regulates DNA repair and genome maintenance.…”
mentioning
confidence: 99%